New data on the genus Supella Shelford, 1911 (Dictyoptera: Pseudophyllodromiidae) with description of female of S. eocenica Anisyutkin et Perkovsky, 2023 from Rovno amber - Anisyutkin, Leonid N.; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2024)
The paper provides a detailed morphological description of a previously unknown female of Supella eocenica Anisyutkin et Perkovsky, 2023. The structure of the tegmina and wings of the type species of the genus Supella, S. longipalpa (Fabricius, 1798), is also redescribed. Ecology of Rovno and Danish amber cockroaches is discussed.